Grain Sorghum Response to Row Spacing and Plant Populations in the Texas Coastal Bend Region - Carlos J. Fernandez; Dan D. Fromme; W. James Grichar (International Journal of Agronomy)
Two grain sorghum (Sorghum bicolor L. Moench) studies were conducted in the Coastal Bend Region of Texas over a two-year period. In one study, sorghum growth and yield were compared when planted in a single row on beds or planted in twin rows on beds with different plant populations under dryland or irrigation. Above average rainfall occurred in May 2000 which resulted in twin rows at any plant population producing higher yields than the single row at lower plant population. In 2001, single-row plantings with either plant population (124,000–160,000 or 161,000–198,000 plants/ha) produced higher yield than twin rows planted at 161,000–198,000 plants/ha. Under irrigation, twin rows planted at 161,000–198,000 plants/ha produced higher yields than single row at the same population; however, no other yield differences were noted when row systems or plant populations were compared. In another study, 38 cm row spacings were compared with 76 cm row spacings under two plant populations. In 2000, when rains fell at an opportune time, no yield differences were noted; however, in 2001 with below average rainfall, the 76 cm plantings at 170,000–200,000 and 210,000–240,000 plants/ha produced higher yield than the 38 cm plantings at those same plant populations.